1981
DOI: 10.13031/2013.34213
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Potential and Corn Yields from Selected Rates and Timing of Liquid Manure Applications

Abstract: A 6-year study was conducted to determine the effects of rate and time of liquid manure application, chemical fertilizer application, and no fertilizer, on the chemical composition of surface and subsurface water and on crop yield. Liquid manure was applied at three rates of 224, 560 and 897 kg/(ha•yr) of N in accordance with four application schedules (i.e. spring, fall, split rates in spring and fall, and winter). In all cases except winter application, manure was incorporated by plowing at time of applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 11 publications
4
15
0
1
Order By: Relevance
“…The 4R Certification Program for agri‐retailers in the Western Lake Erie watershed (Vollmer‐Sanders et al, 2016) is an example of a market infrastructure change required to overcome an obstacle in the avoidance of a time–place combination long known (e.g., Phillips et al, 1981) to pose risk to water quality: the application of P to frozen soil. The 4R certified retailer does not custom apply fertilizer P on frozen or snow‐covered soil.…”
Section: R Transition Managementmentioning
confidence: 99%
“…The 4R Certification Program for agri‐retailers in the Western Lake Erie watershed (Vollmer‐Sanders et al, 2016) is an example of a market infrastructure change required to overcome an obstacle in the avoidance of a time–place combination long known (e.g., Phillips et al, 1981) to pose risk to water quality: the application of P to frozen soil. The 4R certified retailer does not custom apply fertilizer P on frozen or snow‐covered soil.…”
Section: R Transition Managementmentioning
confidence: 99%
“…Phillips et al (1981) have observed that P concentration in surface runoff was higher following winter application of manure than following spring, fall, spring-fall applications or mineral fertilizer treatments. Patni and Culley (1989) have shown that soil P and exchangeable cations were not affected by the method or time of liquid manure application.…”
mentioning
confidence: 97%
“…However, these increased concentrations were at similar or lower levels than those caused by the inorganic fertilizers, especially urea, applied at rates equivalent or even lower than the LCM N (Beauchamp, 1983(Beauchamp, , 1986Comfort et al, 1987;Daliparthy et al, 1994;Jokela, 1992;Lithourgidis et al, 2007;Motavalli et al, 1985;Phillips et al, 1981;Randall et al, 2000). For example, Phillips et al (1981) reported that NO 3 -N concentration in the tile-drain effluent from silage corn receiving LCM at a rate of 897 kg N ha -1 was no greater than that from 134 kg N ha -1 applied as inorganic fertilizer. Beauchamp (1983) found that 560 kg N ha -1 as LCM resulted in less soil NO 3 -N than 208 kg N ha -1 as urea and Beauchamp (1986) reported that application of LCM at a rate of 600 kg N ha -1 did not increase soil NO 3 -N levels above those from urea or the lower LCM application rates.…”
Section: Effect Of Liquid Cattle Manure Application On Soil Propertiesmentioning
confidence: 99%
“…Apart from the beneficial effects of using LCM as an organic fertilizer, certain adverse effects might be involved for plants, soils and the environment upon LCM application to soil; such as increasing salinity in the soil profile, NO 3 -N leaching to the underground water and P accumulation in the top soil (with its subsequent translocation to surface water reservoirs) (Beauchamp, 1983(Beauchamp, , 1986Comfort et al, 1987;Culley et al, 1981;Daliparthy et al, 1994;Evans et al, 1977;Heathwaite et al, 1998;Lithourgidis et al, 2007;Motavalli et al, 1985;Phillips et al, 1981;Pratt & Laag, 1981;Sutton et al, 1979Sutton et al, , 1986Vellidis et al, 1996). These adverse effects are mainly connected to LCM application for long periods and/or at high rates and such applications should be avoided.…”
Section: Introductionmentioning
confidence: 99%